1994
DOI: 10.1093/bja/73.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and pharmacokinetics of an infusion of Org 9487, a new short-acting steroidal neuromuscular blocking agent

Abstract: We have evaluated in 10 anaesthetized patients the time course of action, infusion requirements, reversibility and pharmacokinetics of Org 9487. Org 9487 was administered as a bolus dose of 1.5 mg kg-1, followed by an infusion to maintain a block of 75-85% for 60 min. After recovery from the bolus dose, a mean dose of Org 9487 3.4 (SD 1.0) mg kg-1 h-1 was administered to maintain a mean neuromuscular block of 83 (3)%. During the final 15 min of infusion, the infusion requirements were 2.5 (1.1) mg kg-1 h-1. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

1997
1997
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…As a guide to therapy, infusion requirements of the newer intermediate duration relaxants cisatracurium (CIS) and rocuronium (ROC) have been established. [2][3][4][5][6][7][8][9] However, despite wide inter-patient variability in drug requirements, previous studies have not specifically addressed how infusion rates need to be adjusted as a function of time, during the conduct of anesthesia.…”
Section: Reports Of Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a guide to therapy, infusion requirements of the newer intermediate duration relaxants cisatracurium (CIS) and rocuronium (ROC) have been established. [2][3][4][5][6][7][8][9] However, despite wide inter-patient variability in drug requirements, previous studies have not specifically addressed how infusion rates need to be adjusted as a function of time, during the conduct of anesthesia.…”
Section: Reports Of Investigationmentioning
confidence: 99%
“…However, ROC also has a considerably longer elimination half-life than CIS (t 1/2 ß=60-70 min for ROC, 22-26 min for CIS). 4,7 The present study was therefore designed to compare the time to onset of action, time-related infusion requirements, drug costs, and cumulation potential of CIS vs ROC during procedures of relatively long duration.…”
Section: Reports Of Investigationmentioning
confidence: 99%
“…studies also confirmed the rapid reversibility of the effects of rapacuronium, the times taken to achieve adequate antagonism were generally somewhat longer, particularly with higher doses; this may have been due to the dosage of the drug administered being based on the active moiety. The reduction of dose for maintenance of constant block and the prolonged recovery after a 1-h infusion of rapacuronium suggested the presence of cumulative properties with rapacuronium [21]. This is in contrast to mivacurium, where administration of an antagonist shortens the recovery time only slightly and insignificantly [19].…”
Section: Reversal Of Rapacuronium Blockmentioning
confidence: 98%
“…It is metabolized in the liver primarily to a 3-hydroxy metabolite (Org 9488), which itself is a neuromuscular blocking drug, having twice the potency of rapacuronium (biophase EC 50 0.4 Â rapacuronium) and an intermediate to long duration of action [31]. Excretion of rapacuronium and its metabolites is organ dependent and there is some evidence of cumulation of Org 9488 after repeated doses or an infusion [32].…”
Section: Rapacuroniummentioning
confidence: 99%